As estruturas de sentimento: história e desenvolvimento da noção cultural por Raymond Williams - Oliveira, Luciano Dutra de (2017)
This work has as main purpose to discuss the notion of "Structures of Feeling" developed by Raymond Williams (1921-1988) in the period from 1950 to 1977. Its aim, therefore, is to find such a theoretical formulation in the joint production of the author about themes linked to culture, politics, literature and communication, identifying, in some measure, its historical genesis (especially in his first four books) their development in later works, and deployed aspects of its interpreters, as Terry Eagleton, John Higgins and Fred Inglis. For its proper implementation will be carried out the immanent analysis of all sources (literature, periodicals, newspapers, dissertations, etc.) already consulted in the Raymond Williams Archives (Archives Wales - Swansea University - Wales) on visits from August to September 2013